Perancangan Aplikasi Customer Relationship Management Jasa Service AC di Kota Medan pada CV. XYZ Berbasis Android - Dedi Candro Parulian Sinaga; Baringin Sianipar; Endra Ary Prasasty Marpaung (Prosiding SISFOTEK, 2020)
During the Covid-19 period there were a lot of decreases in AC Service Services in Medan in all companies that did not use online services. This sevice service is difficult to promote by CV. XYZ because it only sticks small banners on the side of the road so that the level of income from the AC Service is not experiencing an increase but has decreased.Customer Relationship Management (CRM) is a business strategy that combines processes, People and Technology. CRM Helps attract sales prospects, convert them into customers, and retain existing customers, satisfied and loyal customers.